2013
DOI: 10.1021/ol4000789
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Addition of N-Hydroxy Heterocycles to Alkynes and Subsequent 3,3-Sigmatropic Rearrangement

Abstract: Gold-catalyzed intermolecular addition of hydroxybenzotriazole derivatives to alkynes at room temperature, gives vinyl ethers 3 in high yields and with excellent regioselectivity. Unlike many other vinyl ethers, 3 can easily be purified by regular silica-gel chromatography. On heating, 3,3-sigmatropic rearrangement of 3 gives access to highly functionalized benzotriazoles. This two-step sequence represents an efficient oxygen transfer protocol which incorporates a nucleophilic oxygen atom into an alkyne group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…We chose the gold‐catalyzed intermolecular addition of N‐hydroxy benzotriazole 4 to an alkyne as our model system for OH addition 15. We were able to reduce the catalytic loading to 0.1 % (Scheme ).…”
Section: Relative Rates Of Hydroamination For Various Ligandsmentioning
confidence: 99%
“…We chose the gold‐catalyzed intermolecular addition of N‐hydroxy benzotriazole 4 to an alkyne as our model system for OH addition 15. We were able to reduce the catalytic loading to 0.1 % (Scheme ).…”
Section: Relative Rates Of Hydroamination For Various Ligandsmentioning
confidence: 99%
“…[15] We were able to reduce the catalytic loading to 0.1 % (Scheme 1 b). This result is a significant improvement over the original literature report (Scheme 1 b), which needed 5 % catalyst loading.…”
mentioning
confidence: 96%
“…During our research to improve the efficiency of gold catalysis, 29,[33][34][35][36] we found this threshold phenomenon is common in gold-catalysed reactions. We studied the correlation between rate and gold catalyst concentration in the cyclization of propargyl amide 4-1 ( Figure 19).…”
mentioning
confidence: 87%
“…Although this phenomenon is ubiquitous in catalysis, relatively little effort has been spent on the investigation of this anomaly and the possible implications of this threshold phenomenon in catalysis. [30][31][32] During our research to improve the efficiency of gold catalysis, 29,[33][34][35][36] we found that this threshold phenomenon is common in gold-catalyzed reactions. We observed during our investigations that high gold affinity impurities (halides, bases) in solvents, starting materials, filtration or drying agents could affect the reactivity of the gold catalyst adversely (Scheme 4), which may significantly reduce the TON of cationic gold catalyzed reactions.…”
mentioning
confidence: 95%